Okul Öncesi Çocuklarda Öz Düzenleme Becerileri ile Anne-Baba Tutumları Arasındaki İlişki Üzerine Bir İnceleme / An Investigation on Relation between Self-Regulation Skills of Pre-School Students and Parental Attitudes - Öztabak, Meryem Esra; Özyürek, Arzu (Journal of History Culture and Art Research, 2018)
Abstract This research aims to investigate the relation between self-regulation skills of pre-school students and the effect of parental attitudes. The subjects of this study consist of 155 children, 79 girls and 76 boys, who were going to the pre-school education institutions affiliated to the Bartın Provincial National Education Directorate and their parents. In order to determine the self regulation skills of the children the “Pre-school Self Regulation Scale” has been applied to the children individually, and to determine the attitudes of the parents the “Family Attitude Inventory” has been used to collect the data. Since there has been no distribution of normality encountered in the test of normality, the Mann-Whitney U test has been used in the two group comparisons, for the correlation between the variables, the Spearman’s rank correlation coefficient has been used. The significance level has been determined as 0,05. As a conclusion, no significant correlation has been detected between the attention/impulse control and positive feeling scores, which are sub-dimensions of self regulation skills, and the sub-dimensions and total score’s of family attitudes inventory. It can be obviously seen that especially the attention and impulse sub dimensions of the pre-school girl students in the experimental group have been more developed and that these children show high self-regulation skills in this sub dimension. It was determined that the parents of the study group had the highest attitudes to identify with their children, followed by social mobility, democratic attitudes and compliance behaviors. Öz Bu çalışmada, okul öncesi periyodundaki çocukların öz düzenleme becerileri ile anne-baba tutumları arasındaki ilişkinin incelenmesi hedeflenmiştir. Çalışma grubunu Bartın İli Millî Eğitim Müdürlüğü’ne bağlı anasınıflarına devam eden 79 kız 76 erkek olmak üzere toplam 155 çocuk ve bu çocukların anne-babaları oluşturmuştur. Verilerin toplanmasında çocukların öz düzenleme becerilerinin belirlenmesinde “Okul Öncesi Öz Düzenleme Ölçeği”, annelerin ve babaların çocuk yetiştirme tutumlarının belirlenmesinde “Aile Tutum Envanteri” kullanılmıştır. Verilerin analizinde, puanlar normal dağılım göstermedikleri için iki gruplu karşılaştırmalarda Mann-Whitney U testi, değişkenler arasındaki ilişkide Spearman’s Brown korelasyon analizinden yararlanılmıştır. Anlamlılık seviyesi olarak 0,05 kullanılmıştır. Çalışma sonucunda; Okul Öncesi Öz Düzenleme Ölçeği Dikkat/Dürtü Kontrolü ve Olumlu Duygu alt boyutları puanı ile Aile Tutum Envanteri alt boyutları ve toplam puanları arasında anlamlı bağlantı bulunmamıştır. Çalışma grubundaki kız çocukların özellikle Dikkat/Dürtü alt boyutu puanlarının daha fazla olduğu, çocukların dikkat/dürtü alanında yüksek düzeyde öz düzenleme becerileri gösterdikleri belirlenmiştir. Çalışma grubundaki anne-babaların, çocuklarıyla özdeşim kurma davranışlarının en yüksek düzeyde olduğu ve bunu sosyal hareketlilik, demokratik tutum ve uyma davranışının izlediği belirlenmiştir.